Uji unjuk kerja mini power thresher tipe pelemparan jerami inovasi masyarakat Kabupaten Sambas - Jagat, Lang; Pridaningsih, Deliana R.; Suhendra, Suhendra; Nopriandy, Feby (Universitas Muhammadiyah Metro, 2024)
Threshing has an important role in rice postharvest activities. Using the wrong threshing technique results in high yield losses. Based on these problems, the people of Sambas Regency developed a power thresher by making a mini power thresher to meet the needs of local farmers. This research was conducted to find information on the specifications and performance of the mini power thresher through verification tests and performance tests. Based on the verification test results, the overall dimensions in the working position are 1,020 mm long, 950 mm wide and 1,170 mm high, the threshing cylinder diameter is 220 mm, and the threshing cylinder length is 690 mm. Based on SNI standards, this mini power thresher is included in the category of small power thresher. The test was carried out on rice of the Inpari variety with a threshing cylinder rotational speed of 650 rpm. Based on the results of the performance test, it was obtained that the feeding capacity was 412.73 kg/hour, the threshing capacity was 164.40 kg/hour, the cleanliness level was 94.54%, the percentage of unhulled grain was 1.75%, the threshing efficiency was 98.25%, the percentage of grain was scattered 0.43%, and the percentage of yield loss is 2.18%. These results indicate that the capacity for feeding and threshing still does not meet the SNI standard criteria for small power thresher.